Are citizens' juries perceived to be legitimate? New survey examines public perception in Colombia - Citizens' Juries in Bogotá (2024)
Over the past few months, our research team has been deeply involved in conducting four Citizens’ Juries in Bogotá. This collaboration between the University of Marburg, the Pontificia Universidad Javeriana in Bogotá, and the International Center for Tropical Agriculture (CIAT) in Cali, focused on important issues related to mitigating carbon footprint in food systems and reversing deforestation in the Colombian Amazon. These juries provided a wealth of quantitative and qualitative data, offering insights into how deliberation affects participants‘ biases and the dynamics within the juries themselves.